COVID-19 the pandemic and what do we know about it? And how Peru faces it. - Karin J. Vera-López (2020)
The novel coronavirus disease 2019 or COVID-19, had been reported for the first time in December 2019, in Wuhan China. To date, around 6 777 435 cases of COVID-19 were confirmed and 395 597 deaths worldwide. The COVID-19 outbreak is the largest in the past decades and is caused by a newly discovered coronavirus (SARS-CoV-2). On March 11th, 2020, the world Health Organization (WHO) has declared the COVID-19 a “Pandemic” with high rate of morbidity and mortality. This review synthesizes the scientific evidence and reports in the literature. The content of this manuscript presents the opinions of specialists and we present our interpretation and recommendations to the Peruvian government.